RSA Blind Signature sebagai dasar pengamanan pada sistem e-voting dengan Prinsip Frictionless User : studi desain dan tinjauan keamanan - Rizky Rahman Judie Putra; Muhamad Nursalman; Ellsya Nabella Nur'allifa (Jurnal Komputer Teknologi Informasi Sistem Komputer (JUKTISI), 2025)
Electronic voting (e-voting) systems have emerged as a critical research topic in the fields of information security and modern election technology. However, various studies have shown that e-voting systems still face several vulnerabilities, particularly in security aspects. One prominent weakness often highlighted is the direct involvement of voters in cryptographic technical processes, such as unblinding, which may lead to negligence and technical errors. This aligns with Bartjan Wattel’s assertion that "The real security challenge lies in protecting business processes from authorized users with malicious intent or who act carelessly" indicating that threats to security do not only originate from external intruders, but often from legitimate users with access rights. This study proposes a solution to minimize the voter’s technical involvement by implementing a Blind Digital Signature protocol based on the RSA algorithm, wherein the entire cryptographic process including blinding, signing, and unblinding is carried out by the system and authorized entities. The goal of the study is to develop an e-voting protocol that reduces voter participation in system security processes (frictionless), and to measure the security level of the implemented protocol. The results show that reducing the voter’s technical role in the cryptographic process enhances security and minimizes errors, as the blinding to unblinding stages are controlled by the system. Moreover, the protocol is modified to include digital signatures during access requests in inter-party communications, preventing forgery and ensuring that only authorized entities can participate in the system.